2001
DOI: 10.1182/blood.v98.6.1732
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of the derivative chromosome 9 occur at the time of the Philadelphia translocation and provide a powerful and independent prognostic indicator in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is characterized by formation of the BCR-ABL fusion gene, usually as a consequence of the Philadelphia (Ph) translocation between chromosomes 9 and 22. Large deletions on the derivative chromosome 9 have recently been reported, but it was unclear whether deletions arose during disease progression or at the time of the Ph translocation. Fluorescence in situ hybridization (FISH) analysis was used to assess the deletion status of 253 patients with CML. The strength of deletion statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
198
8
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(228 citation statements)
references
References 53 publications
18
198
8
4
Order By: Relevance
“…In this paper, the involvement of SDs was proposed to explain the recurrent t(9;22) translocation in CML and the genomic deletions that could accompany the rearrangement. In fact, several groups have previously identified der(9) deletions next to translocation breakpoints as a frequent feature of patients with CML (Sinclair et al, 2000;Huntly et al, 2001;Kolomietz et al, 2001;Storlazzi et al, 2002;Specchia et al, 2004;Albano et al, 2007). To date, the characterization of deletions breakpoints has shown that breaks are scattered throughout large genomic regions, Figure 1 Bioinformatic studies performed on the chromosomes 9 and 22 analyzed regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the involvement of SDs was proposed to explain the recurrent t(9;22) translocation in CML and the genomic deletions that could accompany the rearrangement. In fact, several groups have previously identified der(9) deletions next to translocation breakpoints as a frequent feature of patients with CML (Sinclair et al, 2000;Huntly et al, 2001;Kolomietz et al, 2001;Storlazzi et al, 2002;Specchia et al, 2004;Albano et al, 2007). To date, the characterization of deletions breakpoints has shown that breaks are scattered throughout large genomic regions, Figure 1 Bioinformatic studies performed on the chromosomes 9 and 22 analyzed regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact role of this duplicon in mediating the t(9;22) rearrangement remained mostly speculative. Moreover, it is well known that in 10-18% of patients with CML the t(9;22) is an unbalanced rearrangement, because genomic sequences of chromosomes 9 and 22 are lost during the translocation (Sinclair et al, 2000;Huntly et al, 2001;Kolomietz et al, 2001;Storlazzi et al, 2002). The mechanism on the basis of these genomic microdeletions still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…21 None of the standard medical treatments appear to improve the outcome of patients with deletions of the derivative chromosome 9. 14,15 Moreover, in one study there was also an increased rate of relapse in patients with deletions following allografting. 14 Although the numbers of patients in this study were small (12 patients with deletions and 58 patients who lacked deletions), this finding suggests that allografting may be less effective in achieving disease eradication in patients with deletions of the derivative chromosome 9.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,15 They are associated with an extremely poor prognosis, with those patients who carry them having shorter length of chronic phase, earlier disease transformation, and shorter survival. 14,15 Also, in a direct comparison, deletion status was a far more powerful prognostic indicator than either the commonly used Sokal or Hasford scores. 16,17 Conventional drug treatment for chronic-phase CML includes hydroxyurea and interferon-␣ with or without cytosine arabinoside.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation